Vortex glass phase transition in two-dimensional Bi2Sr2Ca2Cu3O10+δ sub-microbridge. (1st March 2023) - Yu, Aobo; Zhang, Tianzhu; Fan, Donghui; Yuan, Pusheng; Peng, Wei; Li, Hao; Lin, Chengtian; Mu, Gang; Zhang, Xiaofu; You, Lixing
Abstract: Vortex dynamics is crucial for practical applications and to understand the nature of the mixed state for high- T c superconductors. Mechanically exfoliated ultra-thin single crystals provide a unique platform for exploring vortex physics in the two-dimensional (2D) limit. Here, we systematically investigated the current–voltage ( I–V ) characteristics as functions of the temperature and magnetic field in a single-crystalline Bi2223 sub-microbridge of 2.5 unit cells thickness. The nonlinear I–V characteristics are excellently described by the scaling theory for a quasi-2D vortex glass (VG) phase transition, and a phase diagram revealing the VG and vortex liquid phase is drawn. The scaling parameter v is consistent with previous reports, while the critical exponent z is far smaller than that in most investigations. Moreover, the VG transition temperature T g of the present sample is higher than that in the reported Bi2223 epitaxial thin films and tapes. In addition, the pinning force density of our sample is calculated, which is stronger than that reported in Bi2223 epitaxial thin films and tapes. Our results indicate that a high pinning force density may suppress the dynamical critical exponent z and enhance the VG phase transition temperature, providing new insight into the flux dynamics in cuprates.